Mathematical and computational awareness before and after the pandemic - Bubnó, Katalin; Takács, Viktor László (Frontiers in Education, 2022)
Mathematical thinking and computational thinking are going hand in hand. Both of them are based on awareness of problem solving. However, consciousness does not exist without a proper mental and psychological state. Formerly we examined some mathematical psychological aspects that could have an impact both on mathematical and computational problem solving. We taught novice computational programming by solving mathematical word problems. Our first experiments were performed years before the pandemic. In this study, we present the results of a new experiment on the same topic, but this was performed during a pandemic homeschool interval. The programming environment and the teaching material were the same as before. The experiment proved our previous hypothesis that we can successfully teach solving mathematical word problems in a computational environment and at the same time with the help of word problems we can successfully teach the basic elements of computer programming. We present our results based on our homeschool experience. We expect that the results of homeschool study groups are not worse than the results of before-pandemic study groups in reaching the aim above.